Effect of fluoride and gonadal steroid deficiency on enamel and dentin mineralization of female rats Efeito do fluoreto e da deficiência de esteróides gonadais sobre a mineralização de esmalte e dentina de ratas - Eliana Mitsue Takeshita; Sayaka Iwama; Tatiana Correa da Silva; Rita Cássia Menegatti Dornelles; Alberto Carlos Botazzo Delbem; Kikue Takebayashi Sassaki (University of São Paulo, 2004)
The aim of this study was to verify the influence of estrogen deficiency on enamel and dentin microhardness of female rats' incisors, as well as the influence of chronic administration of fluoride on that response. Sham or OVX rats drank distilled water or distilled water with 10 ppm fluoride as NaF, for 90 days. The upper incisors were removed and the specimens submitted to microhardness analysis of enamel and dentin. The data were compared by variance analysis and Tukey's test (p<0.05). There was a significant reduction in the mineralization of crown (7.9% and 8.1%) and root (20.4% and 25.0%) in both groups treated with fluoride or distilled water, respectively and an increase (14.2%) in the mineralization of coronal dentin after ovariectomy. Fluoride treatment did not cause reduction in enamel mineralization; however, it reduced dentin mineralization following ovariectomy. It was possible to conclude that estrogens directly or indirectly influence the process of enamel and dentin mineralization of female rats' incisors. The results also indicate that enamel and dentin exhibit different responses to fluoride administration. O objetivo do trabalho foi verificar se a deficiência de estrógenos causava alteração na microdureza do esmalte e da dentina de incisivos de ratas e se a administração crônica de fluoreto alterava essa resposta. Ratas ovariectomizadas ou sham-ovariectomizadas receberam para beber água destilada contendo ou não NaF 10 ppm, durante 90 dias. Decorrido este tempo, os incisivos maxilares foram removidos e a microdureza determinada no esmalte e dentina. Os resultados foram submetidos à análise de variância e teste de Tukey (p<0,05). Constatou-se uma redução significante na mineralização da coroa (7,9% e 8,1%) e raiz (20,4% e 25,0%) nos grupos tratados com fluoreto ou água destilada, respectivamente e um aumento (14,2%) na dentina da coroa, após a ovariectomia. O tratamento com fluoreto não impediu a redução da mineralização no esmalte, porém interferiu na dentina diminuindo a mineralização, após a ovariectomia. Concluiu-se que o processo da mineralização do esmalte e da dentina dos incisivos de ratas sofre a ação de estrógenos, de maneira direta ou indireta e que os dois tecidos respondem de maneiras diferentes à administração de fluoreto.